Analysis of Students' Understanding of Concepts in Straight Motion Material in Physics Learning - Fitriyani, Fera Maya; Rohmah, Siti; Purnaman, Boby Yasman; Zohuri, Bahman (International Journal of Education and Teaching Zone, 2023)
The research was conducted in order to be able to analyze understanding of concepts in straight motion material. The research that was carried out used a quantitative research type with a descriptive approach to the population of 20 students in physics learning on straight motion material. random sampling technique methods and using instruments in the form of essay questions on straight motion material given to students using a ratio scale with an absolute zero value. Data retrieval analysis technique in which each student is able to solve questions which can be analyzed using 3 indicators, namely: (1) students can restate a concept, (2) utilize arithmetic operations, (3) classify and Students are able to give an example or not an example. The technique used when collecting data is in the form of tests and documentation. The results of this study show that the level of students' understanding of concepts in physics learning is in the category of understanding concepts 25%, not understanding concepts 30%, misconceptions 25%, guessing, 20%